The effect of an increased free fatty acid concentration on thermogenesis and substrate oxidation in obese and lean men - Schiffelers, SLH; Saris, WHM; van Baak, MA (International Journal of Obesity, 2001)
To examine whether a certain increase in plasma free fatty acid (FFA) concentration leads to similar increases in lipid oxidation and energy expenditure in obese and lean men. The study protocol consisted of a 30 min baseline period after which subjects received an i.v. bolus of 1000 IE heparin. Then consecutive infusions of 4.9, 9.8 and 19.6 microl/kg fat-free mass (FFM).min of a lipid heparin mixture were started, each infusion for 30 min. Eleven obese and 13 lean men with a mean body mass index (BMI) of 34.2+/-1.0 (+/-s.e.m.) and 23.9+/-0.5 kg/m(2) and age 46.0+/-1.0 and 42.6+/-1.5 y, respectively. Energy expenditure, respiratory exchange ratio (RER) and carbohydrate and lipid oxidation were continuously measured by indirect calorimetry. At the end of each infusion period, a blood sample was taken for FFA, glycerol, insulin, beta-hydroxybutyrate, noradrenaline and adrenaline determination. At baseline, plasma FFA levels were comparable in both groups. Lipid heparin infusion increased plasma FFA concentration by 301+/-47 micromol/l and 332+/-27 micromol/l in obese and lean men. Energy expenditure increased similarly in obese and lean men (0.34+/-0.08 vs 0.40+/-0.08 kJ/min, NS) during lipid heparin infusion, whereas RER decreased similarly in both groups. Lipid oxidation rates were comparable at baseline and increased similarly in obese and lean men (19+/-5 vs 13+/-4 mg/min, NS). Baseline plasma insulin levels were higher in the obese, but did not change during lipid heparin infusion. Plasma beta-hydroxybutyrate concentrations were similar at baseline, but increased significantly less in the obese during lipid heparin infusion. Baseline noradrenaline and adrenaline concentrations did not differ significantly between groups. During lipid heparin infusion, plasma noradrenaline levels decreased significantly, but plasma adrenaline levels remained unchanged in both groups. A certain increase in plasma FFA concentration leads to similar increases in lipid oxidation and energy expenditure in obese and lean men. The accumulation of fat in obese subjects may therefore be more likely to be due to a defect in adipose tissue lipolysis than a defect in lipid oxidation. International Journal of Obesity (2001) 25, 33-38